2007
DOI: 10.1891/088971807780852039
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory Muscle Training: Integrative Review of Use in Conditions Other Than COPD

Abstract: Inspiratory muscle training (IM training) is a technique that is designed to improve the performance of the respiratory muscles (RMs) that may be impaired in a variety of conditions. Interest in IM training has expanded over the past two decades, and IM training has been used in an increasingly wide range of clinical conditions. However, the benefits of IM training continue to be debated, primarily because of methodological limitations of studies conducted to date. The focus of this article is to provide a cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Studies involving IMT in COPD and heart failure have often reported an improvement in respiratory muscle strength. [24][25][26] In a recent meta-analysis, Gosselink et al 9 examined 32 randomized controlled trials on IMT in COPD and reported a significant effect with an increase in MIP of 13 cmH 2 O. In our study, we found a 26.14 ± 12.15 cmH 2 O (median of 12 cmH 2 O) increase in MIP after IMT.…”
Section: Discussionsupporting
confidence: 50%
“…Studies involving IMT in COPD and heart failure have often reported an improvement in respiratory muscle strength. [24][25][26] In a recent meta-analysis, Gosselink et al 9 examined 32 randomized controlled trials on IMT in COPD and reported a significant effect with an increase in MIP of 13 cmH 2 O. In our study, we found a 26.14 ± 12.15 cmH 2 O (median of 12 cmH 2 O) increase in MIP after IMT.…”
Section: Discussionsupporting
confidence: 50%
“…In addition, we searched the bibliographies of published studies 6,16 . The search was performed in July 2011 and comprised the following terms: " breathing exercises", "inspiratory muscle training", "respiratory muscle training", "heart failure", "congestive heart failure", "heart ventricles", "congestive cardiomyopathy", "ventricular dysfunction" combined with a high sensitivity combination of words used in the search for randomized clinical trials 17 .…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
“…IMT involves the training of muscles that act to expand the chest in order to take air into the lungs 7. It is designed to directly improve the performance of these muscles, which are skeletal in nature and thus trainable 7.…”
Section: Introductionmentioning
confidence: 99%
“…It is designed to directly improve the performance of these muscles, which are skeletal in nature and thus trainable 7. The specific training loads to the inspiratory muscles can be applied with either a non-linear resistive device, a threshold or targeted loading device or normocapnic hyperpnoea; and the training regimens vary in terms of intensity and duration or both 8 9.…”
Section: Introductionmentioning
confidence: 99%